Nutritional ergogenic aids in tennis: A brief review. - Lopez-Samanes, A.; Ortega Fonseca, J. F.; Fernandez Elias, V.; Borreani, S.; Mate-Munoz, J. L.; Kovacs, M. S. (Strength and Conditioning Journal, 2015)
In recent years, the interest of ergogenic aids has grown in the competitive sports arena. As a result, supplementation companies have found a new market and have created an array of products targeting competitive athletes. However, only a few legal supplements have been recognized by scientific literature as being able to enhance performance. These compounds are caffeine, creatine, and bicarbonate. More recently, other substances such as [beta]-alanine and nitric oxide precursors have shown ergogenic effects, but more research is needed. The objective of this review is to provide tennis coaches and sports science researchers the latest information.